2010
DOI: 10.3109/13561820903550804
|View full text |Cite
|
Sign up to set email alerts
|

Nurse-physician collaboration in an acute care community hospital

Abstract: Despite the evidence from the literature of the benefits of collaboration, a collaborative practice model in the acute-care setting remains the exception rather than the dominant practice. The purpose of this study was to evaluate attitudes toward collaboration among nurses and physicians practicing in an acute care community hospital. The sample included 118 nurses and 53 physicians. Background variables of gender, age, education, experience, practice setting, cultural background, and time to interact were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 17 publications
1
45
1
1
Order By: Relevance
“…In general, nurses have a significantly more positive attitude towards collaboration than the physicians (Hojat et. al., 2003;Thomson, 2007;Jones & Fitzpatrick, 2009;Garber etal., 2009;Taylor, 2009;Hughes & Fitzpatrick, 2010;Ashok et al, 2016;Zheng et al, 2016 ).Physicians viewed collaboration as less important when compared with nurses (Rosenstein, 2002;Thomson, 2007;Garber et al,2009;Hughes & Fitzpatrick 2010). Even in different countries like in USA, Israel, Italy, and Mexico, nurses have significantly more positive attitude towards collaboration than that of physicians (Hojat et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, nurses have a significantly more positive attitude towards collaboration than the physicians (Hojat et. al., 2003;Thomson, 2007;Jones & Fitzpatrick, 2009;Garber etal., 2009;Taylor, 2009;Hughes & Fitzpatrick, 2010;Ashok et al, 2016;Zheng et al, 2016 ).Physicians viewed collaboration as less important when compared with nurses (Rosenstein, 2002;Thomson, 2007;Garber et al,2009;Hughes & Fitzpatrick 2010). Even in different countries like in USA, Israel, Italy, and Mexico, nurses have significantly more positive attitude towards collaboration than that of physicians (Hojat et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from communication, respect, and trust, other factors affecting physician-nurse collaboration include understanding of professional roles, task prioritizing and equal power (Tang et al, 2013). Both Physicians and nurses recognize and value effective collaboration as an important element to come up with a quality patient care resulting to improved health outcomes for patients (Rosenstein 2002;Hughes & Fitzpatrick 2010;Robinson et al, 2010). In fact, collaboration and positive relationships between physician and nurse have been identified as major factors contributing to positive patient outcomes and quality patient care (Stein-Parbury, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…8 Studies have demonstrated that effective physician-nurse collaboration improves staff satisfaction and patient health outcomes through shared patient management decisions. 8,9 However, there is a little information available with respect to job satisfaction, process efficiency, or patient outcomes when collaboration and responsibility for patient management are extended to all members of the interdisciplinary team.…”
Section: See the Related Editorial On Page 471mentioning
confidence: 99%
“…68,69 These elements, well-known key factors to attain mutual respect, communication and collaboration among professionals, were significant to understanding professional dignity and its respect for nurses in the settings examined. 70 The collaboration with healthcare assistants was also recognized as an important component that could help nurses to focus on their scope of practice. 71 Support workers were seen as essential to lighten the work strain and overload.…”
Section: Influence Of Workplace Elementsmentioning
confidence: 99%